2021
DOI: 10.1111/1477-8947.12218
|View full text |Cite
|
Sign up to set email alerts
|

How do remittances to the Philippines affect its environmental sustainability? Evidence based on the augmented ARDL approach

Abstract: Remittances to the Philippines constitute a prominent part of its economy. However, remittances' effects on its environment have not been researched. In this regard, this research examines the direct and indirect impacts of remittance inflows on the Philippines' environmental sustainabil-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
1
9
1
Order By: Relevance
“…Regarding the model without asymmetry (Table 7 Panel A), the estimated coefficients indicate that remittances have a positive effect on carbon emissions. Specifically, we find a positive and statistically significant effect of remittances flow on carbon emissions, and this is consistent with the findings of Rahman et al (2019), Kibira (2022) and Karasoy (2021). The long-run results reveal that 1% increase in remittances will lead to an increase in carbon emissions by 0.018%, holding other factors constant.…”
Section: Empirical Findings and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding the model without asymmetry (Table 7 Panel A), the estimated coefficients indicate that remittances have a positive effect on carbon emissions. Specifically, we find a positive and statistically significant effect of remittances flow on carbon emissions, and this is consistent with the findings of Rahman et al (2019), Kibira (2022) and Karasoy (2021). The long-run results reveal that 1% increase in remittances will lead to an increase in carbon emissions by 0.018%, holding other factors constant.…”
Section: Empirical Findings and Discussionsupporting
confidence: 90%
“…Again, Mahalik et al (2021) used the ARDL method from 1978 to 2014 and found that remittances induce carbon emissions in India. Also, Karasoy (2021) established that remittance inflows increase carbon emissions, and hence, pose a threat to environmental sustainability in the Philippines. Furthermore, Kibria(2022) relied on data from 1980 to 2016 and used the NARDL method for Bangladesh to reveal that positive shocks in remittances accelerate carbon emissions while negative shocks in remittances lower carbon emissions in the long term.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, according to (McNown et al, 2018), the assumption of the dependent variable being I (1) needed to tackle the second problem, while the simultaneous significance of the t ‐and F ‐tests can solve the first problem. Thus, in the second case, it is possible to argue that the low power property of unit root tests leads to providing an incomplete co‐integration picture from the analysis (Goh et al, 2017; Karasoy, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The authors justify terrorism's contribution to environmental degradation to its increased energy consumption for armaments, machinery (including those that were used in the production of tanks, ammunition, and weapons), as well as cooking and heating. Another study that examined the Philippines was a study by Karasoy (2021) in which they studied how remittances intensified carbon emissions in the Philippines from the period 1977 to 2016 and found that remittances directly contribute to the increase in carbon emissions in the long run while indirectly through oil consumption and income. Included in this study was the estimation of the impact of FDI on the Philippines' environmental degradation.…”
Section: Still Inmentioning
confidence: 99%